Histopathological Spectrum of Oral Mucosal Lesions in a Tertiary Care Hospital - Shrestha, Bijayata; Subedi, Sushil; Poudel, Suman; Ranabhat, Sunita; Gurung, Geeta (Journal of Nepal Health Research Council, 2021)
Background: Neoplastic as well as non-neoplastic lesions commonly involve oral mucosa. It had been observed that benign lesions were more common than malignant ones. The present study was done to evaluate the pattern of distribution of various oral mucosal lesions in a tertiary care hospital.Methods: This retrospective cross-sectional study reviewed the archival records in the Department of Pathology, Gandaki Medical College, Nepal from January 2017 to December 2020. The records of patients with histopathologic diagnosis of oral mucosal lesions were obtained. The histopathological diagnosis, age, gender, and the site of involvement were collected using a prepared form. Descriptive statistics was applied using SPSS 20 software.Results: Oral mucosal lesions included 3.7% (180 out of total 4895) of cases diagnosed histopathologically. The cases were common among females (101cases/56.1%). Most of the oral mucosal lesions were diagnosed in more than 45 years old patients (75cases/41.7%). The non-neoplastic oral lesions (106cases/58.9%) were the most common lesions followed by neoplastic oral lesions (52cases/28.9%). Among non-neoplastic oral lesions, reactive hyperplastic oral lesions were the most common (50cases/27.8%). Reactive hyperplastic oral lesions frequently affected gingiva (18cases/36%). Neoplastic lesions (Benign neoplasm: 12cases/44.4%; Malignant lesions; 10cases/40%) frequently affected the tongue. Conclusions: Oral lesions were mostly non-neoplastic and reactive hyperplasia being the most commonest presentationKeywords: Neoplastic; non-neoplastic; oral mucosal lesions; reactive